Interpretasi Regulasi Perpajakan Pasca Transformasi Sistem Administrasi Pajak dalam Praktik Akuntansi pada BPR - Sukma Perdana; Agoes Hariyanto; Etty Umamy (JIBEMA: Jurnal Ilmu Bisnis, Ekonomi, Manajemen, dan Akuntansi, 2026)
This study aims to analyze the interpretation of tax regulations in accounting practices at rural banks (Bank Perkreditan Rakyat) in Tulungagung following the transformation of the tax administration system. A qualitative approach was employed using in-depth interviews, observation, and documentation involving accounting practitioners responsible for tax reporting. The findings reveal that the interpretation of tax regulations is not uniform but varies depending on practitioners’ experience, educational background, and organizational context. Such variation is evident in the recognition of fiscal expenses and interest income, reflecting adjustments between regulatory provisions and business practices. The digitalization of the tax system improves reporting efficiency while simultaneously introducing new complexities that require higher adaptive capacity. Furthermore, the linguistic structure of tax regulations influences practitioners’ understanding, leading to differences in application. The study concludes that regulatory interpretation plays a central role in bridging tax policy and accounting practice. This research contributes to the development of an interpretive perspective in tax accounting studies and provides practical implications for improving tax understanding and compliance within rural banks.